Acuity, nurse staffing and workforce, missed care and patient outcomes: A cluster‐unit‐level descriptive comparison. (19th June 2020) - Juvé‐Udina, Maria‐Eulàlia; González‐Samartino, Maribel; López‐Jiménez, Maria Magdalena; Planas‐Canals, Maria; Rodríguez‐Fernández, Hugo; Batuecas Duelt, Irene Joana; Tapia‐Pérez, Marta; Pons Prats, Mònica; Jiménez‐Martínez, Emilio; Barberà Llorca, Miquel Àngel; Asensio‐Flores, Susana; Berbis‐Morelló, Carme; et al.
Abstract: Aim: To compare the patient acuity, nurse staffing and workforce, missed nursing care and patient outcomes among hospital unit‐clusters. Background: Relationships among acuity, nurse staffing and workforce, missed nursing care and patient outcomes are not completely understood. Method: Descriptive design with data from four unit‐clusters: medical, surgical, combined and step‐down units. Descriptive statistics were used to compare acuity, nurse staffing coverage, education and expertise, missed nursing care and selected nurse‐sensitive outcomes. Results: Patient acuity in general (medical, surgical and combined) floors is similar to step‐down units, with an average of 5.6 required RN hours per patient day. In general wards, available RN hours per patient day reach only 50% of required RN hours to meet patient needs. Workforce measures are comparable among unit‐clusters, and average missed nursing care is 21%. Patient outcomes vary among unit‐clusters. Conclusion: Patient acuity is similar among unit‐clusters, while nurse staffing coverage is halved in general wards. While RN education, expertise and missed care are comparable among unit‐clusters, mortality, skin injuries and risk of family compassion fatigue rates are higher in general wards. Implications for Nursing Management: Nurse managers play a pivotal role in hustling policymakers to address structural understaffing in general wards, to maximize patient safety outcomes.